EFFECT OF BIRTH WEIGHT ON MORTALITY AND OCCURRENCE OF DISEASES IN CROSSBRED KIDS - SRIVASTAVA, A. K.; SINGH, CHARAN; KUMARI, SANVENDANA (Indian Journal of Animal Production and Management, 2017)
ABSTRACTRecords of 2001 AB (Alpine X Beetal) and SB (Saanen x Beetal) crossbred kids uptosix months of age were analyzed to study the effect of birth weight on mortality and morbidity.Irrespective of sex average birth weight was 3.06 kg. Male kids had slightly higher (3.140 Â±0.017 kg) than female (2.964 Â± 0.016 kg). The mortality rate for group 1 ( 3.7 kg) were 18.20, 14.57, 14.24 and17.71 %, respectively. In SB male kids, mortality rate was found significantly (P